Failure to consider essential factors keeps former student's suit alive. Issue 3 (May 2016) - Unknown
Abstract : Case name: Dean v. University at Buffalo School of Medicine and Biomedical Sciences, et al., No. 14‐1546‐cv (2d Cir. 10/16/15).